Estimation of Possible Use of Interferon Inductors for Prevention of Postvaccional Reactions to TEOVac in Animal Models - N. K. Chernikova; T. A. Bondareva; S. V. Borisevich; T. V. Dorokhina; A. L. Khmelev; N. V. Shagarova (Антибиотики и Химиотерапия)
The experiments on guinea pigs showed that arbidol administered orally in a single dose 24 hours prior vaccination with TEOVAC and ridostin administered in a single dose intranasally on the 4th day after the vaccination lowered the vaccine virus accumulation in the animal organs and tissue without any effect on the vaccine immunogeneity. The results are someway indicative of the possible use of the interferon inductors for prevention of postvaccinal reactions to TEOVAC.